Skrining dan Edukasi Risiko Kecanduan TikTok pada Anak Sekolah di Jakarta Barat - Ernawati Ernawati; Alexander Halim Santoso; Bryan Anna Wijaya (Pusat Riset dan Inovasi Nasional, 2026)
The rapid rise of short-form social media platforms, particularly TikTok, among adolescents has raised concerns regarding excessive use and potential behavioral addiction that may negatively affect mental health and academic functioning. This community engagement program aimed to screen the risk of TikTok addiction among secondary school students in West Jakarta and provide education on healthy digital practices. The program was conducted at one private school in Jelambar, involving 306 students aged 11–18 years. Screening was performed using the TikTok Addiction Scale (TTAS) followed by digital literacy education. A Plan–Do–Check–Action (PDCA) framework was applied to ensure systematic implementation. The mean TTAS score was 39.97 ± 14.24 (range 20–84), indicating diverse levels of TikTok engagement. Female students demonstrated higher scores and wider distribution, suggesting greater vulnerability to excessive social media use. Digital hygiene and screen-time management education enhanced students’ awareness regarding social media addiction risks and appropriate preventive strategies. This program demonstrated the feasibility and effectiveness of TTAS-based screening for early identification of TikTok addiction risk. It highlighted the importance of integrating digital health promotion into school-based mental health programs to support adolescent well-being.